A report to the Secretary of State for Culture, Media and Sport in response to the European intervention notice : issued on 16 March 2017 in relation to the anticipated acquisition by Twenty-First Century Fox, Inc of Sky PLCA report pursuant to Article 4(2)-(5) of the Enterprise Act 2002 (Protection of legitimate interests) Order 2003.: issued on 16 March 2017 in relation to the anticipated acquisition by Twenty-First Century Fox, Inc of Sky PLCA report pursuant to Article 4(2)-(5) of the Enterprise Act 2002 (Protection of legitimate interests) Order 2003. ([2017]) - Unknown
No abstract available